Under the radar? - Bullock, Karen (2023)
The UK's tourism and hospitality industries, having the highest concentration of migrant workers compared to other industries, face complex challenges in managing the risks of labour exploitation and modern slavery (MS); issues largely neglected in academic research. New employment models risk weakening workers' power in employment relations, potentially leading to increased vulnerability and exploitation risk. Based on analysing primary and secondary sources, this article examines the nature of these risks. Our findings show the following drivers: power imbalances; possible enforcement gaps; normalisation and moralisation of possible exploitation; and potential threats posed by macro-level political and socioeconomic issues/events; these, including more competitive labour markets, paradoxically also present opportunities. We develop significant, novel theoretical contributions and propose the new ‘(in)conspicuous exploitariat’ concept, encapsulating their (dis)empowerment, and potential future risks/opportunities. The research advances theory, with implications for policy and practice, for both the UK and the international tourism and hospitality industries.